Between the Archive and the Feed - Bilyana Palankasova (A Peer-Reviewed Journal About)
This article discusses feminist performance and internet art practices of the 21st century through the lens of Boris Groys’s theory of innovation. It analyses works by Signe Pierce, Molly Soda, and Maya Man, to position practices of self-documentation online in exchange with feminist art histories of performance and electronic media. The text proposes that the discussed contemporary art practices fulfil the process of innovation detailed by Groys through a process of re-valuation of values via an exchange between the everyday, trivial, and heterogenous realm of social media (‘the profane’) and the valorised realm of cultural memory (‘the archive’). Using digital ethnography and contextual analysis, framed by the theory of innovation, the text introduced ‘content value’ as a feature of contemporary art on the Internet. The article demonstrates how feminist internet art practices expand on cultural value through the realisation of a process of innovation via an intra-cultural exchange between the feed and the institution.